Sericulture has been long time in South Sulawesi become one of agriculture activities. Silk clothes is a tradition in South Sulawesi culture. South Sulawesi is the main producer of cocoon and raw silk in Indonesia. In recent years, the production of cocoon and raw silk was decreasing because of many factors, while demand of raw silk for weaving industry was increasing. The purpose of this study are to find the relation among institution, conduct and performance of sericulture activity, to fi - Andi Sadapotto; Hariadi Kartodihardjo; Hermanu Triwidodo; Dudung Darusman; Mappatoba Sila (Forum Pasca Sarjana, 2010)
Sericulture has been long time in South Sulawesi become one of agriculture activities. Silk clothes is a tradition in South Sulawesi culture. South Sulawesi is the main producer of cocoon and raw silk in Indonesia. In recent years, the production of cocoon and raw silk was decreasing because of many factors, while demand of raw silk for weaving industry was increasing. The purpose of this study are to find the relation among institution, conduct and performance of sericulture activity, to find institutional arrangement of sericulture, to find incentive that can improve efficiency and performance of sericulture. The study was carried out in Enrekang and Soppeng of South Sulawesi and Luoding City of Guangdong Province, China. Data were collected using structured interviews, direct observation and documentations. The sample was consisted of 84 farmers, 3 civil servants, 2 sericulture experts, 2 egg producers, drawn using combination of random sampling and purposive sampling. The result of the study show that the difference in performance of sericulture in South Sulawesi and Guangdong because the difference in contract agreement between farmer and cocoon buyer, which make the the conduct of the farmer in Guangdong more consistent in their farming. Sericulture in South Sulawesi need to arrange their economic institution to improve their performance. Key words: institutional arrangement, sericulture, performance, South Sulawesi